The Influence of Management Innovation, School Ethos and Community Involvement on School Quality - Cahyani, Arini Dwi; Arbarini, Mintarsih; Mulyono, Sungkowo Edy; Ilyas; Yusuf, Amin (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
Community Learning Activity Centers (PKBM) are known to be of low quality and have minimal achievement of school quality indicators. This study demonstrates the direct and indirect influence of management innovation, school ethos, and community involvement on school quality. The sampling technique was stratified cluster random sampling, with a sample size of 400 administrators spread across 15 East Java Province, Indonesia cities. The research design used a quantitative approach with a structured equation model (SEM). Data collection used questionnaires, observation, and documentation. The results showed that management innovation, school ethos, and community involvement significantly influenced school quality. Management innovation implemented by the principal and management team was proven to increase the efficiency and effectiveness of the learning process and school governance. The high school ethos is reflected in teacher enthusiasm, student discipline, and a positive culture within the school environment, directly impacting educational service quality. Meanwhile, community involvement from parents, the school committee, and the surrounding environment strengthens support for school programs, both in material and moral aspects. These three variables simultaneously contribute to improving school quality, both in terms of student academic achievement, availability of facilities and infrastructure, and the school's reputation in the eyes of the community.